Pembelajaran Berdiferensiasi: Model Station Rotation untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa Pada Materi Pemanasan Global - Tsaqafah, Pustaka Fitrah; Maryanti, Sri; Listiawati, Milla (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze learning with and without differentiated learning using the station rotation model to improve students' creative thinking skills on global warming material. This research method is quantitative with a quasi-experimental design. The research sample consisted of 54 samples consisting of two research groups, namely the control and experimental groups and each class consisted of 27 students. Data collection was based on tests taken with subjective test types, namely essay tests based on creative thinking indicators. The improvement of creative thinking skills on global warming learning materials in classes with and without differentiated learning using the station rotation model based on the results of the N-Gain of the experimental class has a fairly effective criterion with an N-Gain value of 0.62 in the experimental class and 0.42 in the control class. Differentiated learning using the station rotation model to improve students' creative thinking skills has a positive and significant effect on improving students' creative thinking skills on global warming material. Thus, this research is quite effective and significant if applied in learning at school.